1996
DOI: 10.1007/s001250050440
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of development of peripheral neuropathy in streptozotocin-induced diabetic rats with N-acetylcysteine

Abstract: N-acetylcysteine (NAC) is a precursor of glutathione (GSH) synthesis, a free radical scavenger and an inhibitor of tumour necrosis factor alpha (TNF). Because these functions might be beneficial in diabetic complications, in this study we examined whether NAC inhibits peripheral neuropathy. Motor nerve conduction velocity (MNCV) was significantly decreased in streptozotocin-induced-diabetic Wistar rats compared to control rats. Oral administration of NAC reduced the decline of MNCV in diabetic rats. Structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 0 publications
1
30
0
Order By: Relevance
“…NAC and ALA are known to act as potent antioxidants in diabetic complication (Maritim et al 2003;Sagara et al 1996). Our previous study also demonstrated that NAC prevents oxidative cell damage of HIT-T15 pancreatic beta cell induced by the reducing sugar 2-deoxy-D-ribose (Koh et al 2005).…”
Section: Discussionmentioning
confidence: 93%
“…NAC and ALA are known to act as potent antioxidants in diabetic complication (Maritim et al 2003;Sagara et al 1996). Our previous study also demonstrated that NAC prevents oxidative cell damage of HIT-T15 pancreatic beta cell induced by the reducing sugar 2-deoxy-D-ribose (Koh et al 2005).…”
Section: Discussionmentioning
confidence: 93%
“…The effects of ARIs on indices of DN are unidirectional with those of inhibitors of nonenzymatic glycation (57,65,77) and PKC (62,78) as well as antioxidants (31,55,64,70,(79)(80)(81)(82)(83). Over past several years, the continuing debate about a "primary mechanism" of diabetic complications has centered on oxidative stress and its relationship with other hyperglycemiainitiated factors (84).…”
Section: Discussionmentioning
confidence: 99%
“…substance P and neuropeptide Y deficits in the sciatic nerve that were, at least partially, counteracted by α-lipoic acid [208]; 2) taurine alleviated oxidative stress and prevented diabetes-induced nerve growth factor deficit in the sciatic nerve of STZ-diabetic rats [191]. Several studies implicate oxidative/nitrosative stress in morphological abnormalities characteristic for PDN as well as neuronal apoptosis [177,179,209] Despite evidence for an important role of oxidative/nitrosative stress in the pathogenesis of experimental PDN, conventional antioxidants (e.g., lipoic acid) have modest [186,187] effect on clinical neuropathy. Note, that in animal studies, such conventional antioxidants as vitamin E, butylated hydroxytoluene and N-acetyl-L-cysteine had to be administered at extremely high doses of 0.5-1 g/kg body weight per day to produce effect on PDN.…”
Section: Diabetic Neuropathymentioning
confidence: 97%